2012
DOI: 10.2119/molmed.2011.00425
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-SMA by the Ectodomain of FGFR2c Attenuates Lung Fibrosis

Abstract: The soluble ectodomain of fibroblast growth factor receptor-IIIc (sFGFR2c) is able to bind to fibroblast growth factor (FGF) ligands and block the activation of the FGF-signaling pathway. In this study, sFGFR2c inhibited lung fibrosis dramatically in vitro and in vivo. The upregulation of α-smooth muscle actin (α-SMA) in fibroblasts by transforming growth factor-β1 (TGF-β1) is an important step in the process of lung fibrosis, in which FGF-2, released by TGF-β1, is involved. sFGFR2c inhibited α-SMA induction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Although this study showed a positive effect of Fgf2 on lung repair, it has also been reported that activation of FGFR signaling in pulmonary fibroblasts promotes fibrosis, as demonstrated by the reduced bleomycin-induced fibrosis in mice with combined inducible knockout of Fgfr1, Fgfr2 and Fgfr3 in fibroblasts (Guzy et al, 2017). A similar effect has been observed upon treatment of wild-type mice with a soluble Fgfr2c ligand trap, which inhibits signaling by the FGFs that activate stromal cells (Ju et al, 2012). Therefore, the repair-promoting effects of FGFs are unfortunately associated with induction of fibrosis through the action of FGFs on fibroblasts.…”
Section: Fgf Signaling In Lung Intestine and Liver Repair Fgf Signalsupporting
confidence: 68%
See 1 more Smart Citation
“…Although this study showed a positive effect of Fgf2 on lung repair, it has also been reported that activation of FGFR signaling in pulmonary fibroblasts promotes fibrosis, as demonstrated by the reduced bleomycin-induced fibrosis in mice with combined inducible knockout of Fgfr1, Fgfr2 and Fgfr3 in fibroblasts (Guzy et al, 2017). A similar effect has been observed upon treatment of wild-type mice with a soluble Fgfr2c ligand trap, which inhibits signaling by the FGFs that activate stromal cells (Ju et al, 2012). Therefore, the repair-promoting effects of FGFs are unfortunately associated with induction of fibrosis through the action of FGFs on fibroblasts.…”
Section: Fgf Signaling In Lung Intestine and Liver Repair Fgf Signalsupporting
confidence: 68%
“…Reduces susceptibility to hyperoxia and promotes lung recovery Promotes alveolar regeneration in a long-term injury model Promotes recovery after bleomycin-induced or naphthalene-induced injury Hokuto et al, 2004Perl and Gale, 2009Guzy et al, 2015Guzy et al, 2017Ju et al, 2012 Continued…”
Section: Fgfr2b Fgf2mentioning
confidence: 99%
“…Our results showed that the therapy of RAPA treatment for 14 d could ameliorate progressive pulmonary fibrosis, and the antifibrotic effects were more obvious in the lung tissues of the mice given RAPA for 28 d. The more rapid effect of RAPA compared with DHA (35 d) and naringin (21 d) suggests that RAPA treatment may have a more potent anti-fibrogenesis impact. The key effector cells in the development of pulmonary fibrosis are myofibroblasts (Wang et al, 2012), which are thought to arise from proliferation or differentiation of resident lung fibroblasts, epithelial-to-mesenchymal transition (EMT) and recruitment of circulating fibrocytes (Tulek et al, 2011;Kendall and Feghali-Bostwick, 2014). Various cytokines, growth factors, and signaling pathways are involved in these events.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a key fibrogenic cytokine, which plays a critical role in the expression of α-smooth muscle actin (α-SMA) and induction of lung fibrosis (Oka et al, 2013). α-SMA is the hallmark of myofibroblasts, which are generally considered to be the key effector cells in the development of fibrosis (Wang et al, 2012). The aim of this study was to evaluate RAPA treatment as a potential novel therapy for attenuating PQ-induced pulmonary fibrosis by assessing its effects on the survival rate, body weight, histology, and hydroxyproline (HYP) content of PQ-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…FGFR2c ligands are generally regarded as profibrotic, as they induce fibroblast proliferation and myofibroblast differentiation. Inhibition of FGFR2c ligand activity by overexpressing a decoy receptor inhibits smooth muscle actin ( Acta2 ) expression and attenuates bleomycin‐induced pulmonary fibrosis in mice (Ju et al, ; Yu et al, ). However, mesenchymal FGF signaling is not necessarily profibrotic.…”
Section: Introductionmentioning
confidence: 99%